Hubungan Gelombang Cahaya Lampu dan Cahaya Biru dengan Kualitas Tidur Remaja Dewasa - Hidayat, Muhamad Taufik; Nurmaulid, Aghnia; Wulandari, Dhea Suci; Muto'an, Adha Syarief; Aditya, Danda (Universitas Palan, 2024)
Sleep is a crucial part of the human circadian cycle. The quality and quantity of sleep significantly influence various aspects of health, both physical and psychological. The hormone melatonin, which plays a vital role in sleep regulation, is produced as the intensity of light received by the eyes decreases. Currently, the use of lights and electronic devices emitting blue light is widespread, especially among teenagers to adults. This blue light can interfere with the production of melatonin, potentially disrupting sleep quality and patterns. In this age group, most are active students with busy schedules. This study uses a sequential explanatory design approach, combining quantitative and qualitative questionnaires to collect data and measure the impact of light on sleep duration and patterns. The respondents of this study were 71 people, coming from various universities and different study programs in Bandung City, ranging in age from 18 to 25 years. The research data results show that 38.6% of respondents experience sleep disturbances when the light is on, impacting sleep quality. Conversely, sleep quality improvement occurs in 81.4% of respondents when sleeping with the light off. The use of night mode on electronic devices, designed to reduce blue light emissions, positively impacts sleep quality, as felt by 38% of the 67.1% of respondents who use the night mode feature.